Life enhancement of bent pipe by heat treatment. (2022) - Maitra, Abhishek; Kumar, Randhir; Kulkarni, T.B.; Srikanth, S.; Kumar, S.; Jha, S.K.
Abstract: Wire rod mill is continuous high speed rolling mill to produced wire rods of varying diameters from billets. Bent pipe is a thick-walled hollow pipe located in between the pinch roll and laying head of the wire rod mill, which feeds wire rod from mill to the laying head. The pipe is not straight and the bending of the pipe is designed in such a manner so that it can accommodate the height difference between the pinch roll and the laying head in the WRM. Bent pipe absorbs lot of mechanical shock due to its shape and it absorbs thermal shock as finish rolling temperature is around 1000 °C. Thus, significant abrasive wear of bent pipe takes place during operation as a result it punctures almost regularly after around 1200 T of rolling. This kind of failure of bent pipe is predominant in lower section plain wire rods which are rolled at relatively higher speed. The puncture of bent pipe during rolling leads to cobble and production losses. The failed bent pipe was investigated by metallurgical investigations. JMat pro software was used to determine the CCT diagram from where the maximum hardness of material was determined. Heat treatment experiments were performed in laboratory to optimize the heat treatment parameters. After proper heat treatment, life of bent pipe was improved by using the existing material by 150%. This was validated by plant trials.